The Role of Factor VII in Haemostasis: Infusion Studies of Factor VIIa in a Canine Model of Factor VIII Deficiency - Mertens, Koen; Briët, Ernest; Giles, Alan R (Thrombosis and Haemostasis, 1990)
The role of factor VIIa in haemostasis has been studied using a canine model of factor VIII deficiency. Highly purified human factor VIIa was administered to dogs at a dosage of 0.5 μg/kg. At selected times pre- and post-infusion, haemostasis was evaluated by the cuticle bleeding time. Plasma was collected for the assay of various parameters, including fibrinopeptide A (FPA) as a marker for thrombin generation in vivo. Factor VIIa infusion resulted in a 6-fold increase of factor VII clotting activity with z t1/2 of 2 h. FPA levels which were 1.4 ng/ml before infusion, did not increase significantly in haemophilic dogs. In normal dogs, however, FPA levels rose to a mean value of 190 ng/ml 30 min post-infusion. It appeared that thrombin generation by factor VIIa infusion had occurred mainly via the intrinsic, factor VIIIdependent pathway. In factor VIII-deficient dogs, factor VIIa infusion did not correct cuticle bleeding, but an inconsistent haemostatic effect was observed 15–30 min post-infusion. Similar results were obtained in haemophilic dogs with circulating antibodies against factor VIII. The haemostatic effectivity could not be improved by increasing the factor VIIa dosage up to 40-fold. Although these data suggest that the extrinsic, factor VIIdependent factor X activation provides only a minor pathway of thrombin generation in vivo, it is possible that the suboptimal haemostatic effect noted may be promoted in bleeding situations where tissue factor availability is less limited. As such, factor VIIa may prove useful in the treatment of haemophilia A patients with acquired inhibitors to factor VIII.